(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The development of Medical English proficiency has become an important pedagogical issue in medical higher education, especially in non-English-speaking contexts where students are expected to read scientific literature, understand international terminology, participate in academic communication, and communicate professionally in health-related situations. This article analyzes the main problems that medical university students face while learning English and proposes effective strategies for improving their Medical English proficiency. The study is based on a narrative review of research on English for Specific Purposes, English for Medical Purposes, English- medium medical education, digital learning, and AI-supported language instruction. The analysis shows that the most common challenges include complex medical terminology, low or uneven general English proficiency, insufficient speaking and writing practice, limited contextualization of tasks, weak connection between English lessons and medical subjects, and assessment practices that do not always reflect professional communication needs. The article argues that Medical English instruction should be needs-based, context-sensitive, interdisciplinary, communicative, and supported by carefully selected digital tools. It recommends integrating authentic medical texts, clinical role-plays, case-based tasks, terminology training, academic writing practice, blended learning, and responsible AI-supported feedback into the curriculum. The findings may be useful for English language teachers, curriculum designers, and medical universities seeking to modernize foreign language education for future healthcare professionals.